Negatively Regulated by miR-29c-3p, MTFR1 Promotes the Progression and Glycolysis in Lung Adenocarcinoma via the AMPK/mTOR Signalling Pathway - Li, Yongmeng; Liu, Yanfei; Jin, Kai; Dong, Rui; Gao, Cun; Si, Libo; Feng, Zitong; Zhang, Huiying; Tian, Hui (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background: Lung adenocarcinoma (LUAD) is the major form of lung cancer that presents a major peril to public health. Owing to the high rates of morbidity, mortality and chemoresistance, it is necessary to develop more effective therapeutic targets of LUAD. Mitochondrial fission regulator 1 (MTFR1) affects the occurrence and development of some diseases by regulating mitochondrial dynamics and is dysregulated in LUAD. However, the functions and molecular mechanisms of MTFR1 in LUAD have not been investigated. Methods: Immunohistochemical (IHC) analysis, real-time quantitative polymerase chain reaction (RT-qPCR), bioinformatic analysis and western blot (WB) were performed to assess the expression of MTFR1 at both protein and mRNA levels. The biological functions of MTFR1 in LUAD cells were assessed based on various in vivo and in vitro experiments. The dual-luciferase reporter assay and some rescue experiments were performed to evaluate the underlying mechanism of MTFR1 in LUAD. Results: MTFR1 was upregulated in LUAD cells and tissues and correlated with dismal clinicopathologic features and a worse prognosis of patients with LUAD. Functionally, MTFR1 overexpression stimulated the proliferation, invasion, migration and glycolytic capacity and impeded the apoptosis of LUAD cells; however, opposite results were obtained when MTFR1 expression was knocked down. MTFR1, which was directly targeted by miR-29c-3p, may exert its biological functions through the AMPK/mTOR signalling pathway. Conclusions: MTFR1 promotes the progression of LUAD. Therefore, targeting MTFR1 can offer an effective therapeutic strategy for LUAD treatment.